SAWER SUNDA DALAM PERSPEKTIF FUSI HORIZON STUDI HERMENEUTIKA GADAMER - Ahmad Maki Maki (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
Sawer Sunda is a form of oral literature that persists as a functional element in various traditional rites, particularly marriage ceremonies. This tradition serves not only as a ritual supplement but also as a medium for transmitting moral, social, and religious values within Sundanese society. This study aims to examine the meaning of Sawer Sunda as a cultural text and to explain how Islamic values interact with local traditions to shape the identity of the Sundanese Muslim community.Using a qualitative approach, the research employs text analysis and Hans-Georg Gadamer’s hermeneutics, specifically the concept of the fusion of horizons. The research data consists of sawer texts collected from wedding ceremonies and written documentation, which were then analyzed through thematic grouping and interpretative reading.The results indicate that Sawer Sunda functions as a living tradition embodying educational, social, and religious roles. The meaning of sawer is not static; rather, it is formed through a dialogue between the "horizon" of Sundanese tradition and the "horizon" of contemporary Islamic understanding. This fusion of horizons produces a new interpretation wherein custom (adat) and Islam reinforce one another, particularly in establishing household ethics, social harmony, and religious consciousness. Consequently, sawer represents a Sundanese Islamic character that is contextual, moderate, and deeply rooted in local culture. This research contributes to the development of Sundanese literary studies and Islam Nusantara by offering a hermeneutic approach as an analytical alternative. Practically, these findings are relevant to local cultural preservation, wisdom-based education, and the strengthening of cultural da'wah (proselytization) in modern society.